The Relation between CEO Compensation and Past Performance - Banker, Rajiv D.; Darrough, Masako N.; Huang, Rong; Plehn-Dujowich, Jose M. (The Accounting Review, 2013)
ABSTRACT: This study focuses on the relation between current compensation and past performance measures as signals of a chief executive officer's (CEO's) ability. We develop a simple two-period principal-agent model with moral hazard and adverse selection and test theoretical predictions using CEO compensation data from 1993–2006. Consistent with the predictions, we find that salary (bonus) is positively (negatively) associated with past performance for both continuing and newly hired CEOs. We also find that while current salary is positively associated with future performance, current bonus is not. As the model suggests, salary is adjusted to meet the reservation utility and information rent, and is positively correlated over time to reflect ability. Bonus serves to address moral hazard and adverse selection by separating high-ability agents into riskier contracts. Our results indicate that it is important to disaggregate cash compensation into salary and bonus components to understand the dynamic interaction between incentives and performance. Data Availability: Data are available from public sources indicated in the text.